MAKING SOAP FROM DURIAN FRUIT PEEL EXTRACT - Arsa, Abdullah Kunta; Achmad, Zubaidi (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
Antibacterial bath soap is one of the liquid cleansing preparations made from basic ingredients and is used to clean the skin with the main benefit of effectively killing bacteria and other types of microorganisms so as to minimize skin irritation. Durian fruit skin contains alkaloids, flavonoids, steroids, triterpenoids, and tannins as antibacterial compounds and saponins that can produce foam in water. The main objective of this research is to formulate antibacterial bath soap from durian fruit peel extract. This type of research is an experiment, carried out by Soxhlet extraction of durian skin using 20%, 40%, 60%, 80%, and 96% methanol as solvent. The antibacterial bath soap formula was made at a concentration of 25% durian skin extract including formulas F, G, H, I, and J using a differentiating ingredient, namely the durian skin extract, and was tested for physical and chemical evaluations including organoleptic, homogeneity, pH, foam height, and irritation test. For the results of the remaining durian skin extract, organoleptic tests will be carried out which include texture, color, and the presence or absence of fungi on the storage time of durian skin extract. The results showed that antibacterial bath soap from durian peel extract had met the requirements for a stable physical-chemical evaluation test which included pH, foam height, and irritation test as well as organoleptic and homogeneity tests for formula F.